Utilizing e-commerce platforms as a tool for online business practicum - Mochamad Agung Wibowo; Deborah Juniar Debbi; Novti Nurlaila Ramadhanti (Curricula: Journal of Curriculum Development, 2024)
In the rapidly advancing digital era, the role of e-commerce platforms in the business world cannot be ignored. In education, particularly at the vocational school (SMK) and higher education levels, instruction on e-commerce and online marketing is increasingly crucial. This is closely related to the need to equip students with skills and knowledge relevant to the ever-changing business landscape. This research aims to identify the utilization of e-commerce as a tool for online business practicum at SMK Pasundan 1 Bandung. The methodology employed is descriptive, using a quantitative approach. The study reveals an innovative concept that leverages e-commerce platforms for practical business learning at SMK Pasundan 1 Bandung. This approach signifies a vocational school business education breakthrough, emphasizing practical application in online business operations. Fortunately, after incorporating e-commerce as a learning tool, students are motivated to learn, and the study materials become more comprehensible at SMK Pasundan 1 Bandung. This utilization is expected to prepare students for the increasingly digital demands of the workforce.